REVITALISASI NASKAH SYAIR: SEBUAH SOLUSI DALAM PENGEMBANGAN KREATIVITAS MAHASISWA UNTUK MENCINTAI BUDAYA LOKAL - Tuti Andriani (Sosial Budaya, 2014)
Cultures were grown in campus tend to imitate the western culture, so that the local culture is ruled out. The local culture is considered ancient culture, so it does not show up in the form of creativity. Though Indonesia is rich with culture can be preserved in the campus. One of them is a manuscript poem, which is one form of the local culture of our nation. The text of the poem can be in the form of creative songs, drama, dance and others. One solution is to develop student creativity with the revitalization (revive) the text of the poem and developed through programs of student organizations in the field of arts and culture. So it is the first step to develop a sense of love of local culture